Formulasi Sediaan Masker Peel Off dari Ekstrak Buah Alpukat (Persea Americana Mill.) dengan Variasi Konsentrasi Polivinil Alkohol (PVA) - Ririn Ririn; Vina Purnamasari M; Nurfajeriani Ulfah (Journal of Pharmaceutical and Health Research, 2023)
Face mask peel off is a skin care product that when applied to the skin will dry out which can be peeled off from the skin of the face. Avocado Flesh (Persea americana Mill.) has powerful antioxidants that can be used in moisturizing and anti-aging products. This study aims to produce mask preparations to peel off gel from avocado fruit extract (Persea americana Mill.) to moisturize facial skin. This study used the maceration method to obtain a thick extract from avocado fruit. Mask formulation peel off made in a variety of polyvinyl alcohol (PVA) bases, namely 10% (F1), 12% (F2) and 14% (F3) as a film-forming agent. The evaluation is based on physical parameters including organoleptic, homogeneity, spreadability, pH, viscosity, flow properties, drying time and measurement of facial skin moisture levels. The evaluation results on the pH test, homogeneity and drying time showed that all formulas met the standard parameters, namely the PVA pH test 10% = 6.46; PVA 12% = 6.4; PVA 14% = 6.35, in the long test the drying time of 10% PVA = 18.97 minutes; PVA 12% = 20.82 minutes; and 14% PVA = 24.66 minutes. Meanwhile, in the organoleptic test,viscosity, the three formulas were pharmaceutically unstable, namely in the organoleptic test the three formulas experienced a change in consistency, in the spreadability test the spreadability value of PVA 10% = 5.41; PVA 12% = 4.75; PVA 14% = 4.03, in the viscosity test of the three formulas after forced conditions = E (error: the viscosity value exceeds the maximum limit of the viscometer). Based on the results of the facial skin moisture test, it shows that Avocado fruit extract with a concentration of 0.6% can provide effectiveness as a moisturizer for facial skin.